2011
DOI: 10.1016/j.ejca.2011.06.038
|View full text |Cite
|
Sign up to set email alerts
|

Influence of body mass index on outcome in advanced colorectal cancer patients receiving chemotherapy with or without targeted therapy

Abstract: These results show that BMI is an independent prognostic factor for survival in patients receiving chemotherapy, but not in patients receiving chemotherapy and targeted therapy. The possible decreased efficacy of bevacizumab in obese patients may explain this discrepant result. The role of BMI in patients receiving targeted therapy should be further tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
65
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 25 publications
5
65
3
1
Order By: Relevance
“…However, the lack of effective prognostic prediction markers to stratify the patients remains a major challenge to establish an optimal personalized treatment paradigm of using these antiangiogenic agents to date. In a continuous effort to identify more effective prognostic markers, 'adiposity' has recently attracted research interest as a potential clinical biomarker to evaluate the efficacy of applying VEGF-targeted antiangiogenic therapy to treat a variety of cancers, including colon cancer (7,19), renal cell carcinoma (20,21) and ovarian cancer (9). However, previous studies generated somehow conflicting results (7,19,20,21).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…However, the lack of effective prognostic prediction markers to stratify the patients remains a major challenge to establish an optimal personalized treatment paradigm of using these antiangiogenic agents to date. In a continuous effort to identify more effective prognostic markers, 'adiposity' has recently attracted research interest as a potential clinical biomarker to evaluate the efficacy of applying VEGF-targeted antiangiogenic therapy to treat a variety of cancers, including colon cancer (7,19), renal cell carcinoma (20,21) and ovarian cancer (9). However, previous studies generated somehow conflicting results (7,19,20,21).…”
Section: Discussionmentioning
confidence: 81%
“…In a continuous effort to identify more effective prognostic markers, 'adiposity' has recently attracted research interest as a potential clinical biomarker to evaluate the efficacy of applying VEGF-targeted antiangiogenic therapy to treat a variety of cancers, including colon cancer (7,19), renal cell carcinoma (20,21) and ovarian cancer (9). However, previous studies generated somehow conflicting results (7,19,20,21). In the present study, a CAD approach was developed for the first time to quantitatively extract adiposity-related image features and to demonstrate the feasibility of applying multivariate data analysis models to stratify EOC patients with and without potential clinical benefit by receiving maintenance bevacizumab-based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…This might explain slightly better outcomes in obese patients receiving bevacizumab in our cohort of patients evaluated. However, other studies have shown contradictory results, postulating decreased efficacy of bevacizumab in obese patients [13,20,21]. In fact, response rates, time to progression as well as survival was worse in patients receiving bevacizumab with a higher BMI [21].…”
mentioning
confidence: 82%
“…In fact, response rates, time to progression as well as survival was worse in patients receiving bevacizumab with a higher BMI [21]. The authors speculate it might be higher circulating levels of VEGF conferring resistance to bevacizumab alongside higher volume of distribution in obese patients [13]. Furthermore, in another study, obese patients with colon cancer were less likely to have deficient mismatch repair status (10 vs 17%, p-value <0.001), which maybe another factor affecting outcome in these patients [22].…”
mentioning
confidence: 99%
See 1 more Smart Citation